Sustaining High Value Agricultural Products in Cold Storage Systems in India: Mitigation of Environmental Impact through Alternative Energy-Mix - Saha , Anindita Roy (Journal of Postharvest Technology, 2022)
With the changing consumption pattern, people’s demand for high-value agricultural products (HVAP), such as meat, fish, eggs, fruits, vegetables, milk, and milk products, has been increasing in India in recent decades. This has led to a growth in the production of HVAP and an increased requirement for cold storage, which currently has an installed capacity of 37.5 million tons. The cold storage sector, which primarily uses vapor absorption and vapor compression technologies, is a significant consumer of energy and a potential cause of environmental degradation in India. This sector consumes 6 percent of the annual electrical energy output and produces 2.35 percent of carbon dioxide emissions in the country. Based on the changing consumption patterns and production trends of HVAP, the current study makes projections for the production of HVAP, required cold storage capacity, resultant energy consumption, and carbon dioxide emissions for 2030, 2040, and 2050. The study further shows that the use of an alternative energy mix through a switch from non-renewable to renewable energy can significantly reduce the share of the cold storage sector in total emissions to a mere 0.41 percent by 2050, thereby improving India’s energy and emissions future.